Trânsito na capital amapaense: a solução ainda é a educação - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2010)
This Course Completion Work is born with the purpose of analyzing a social fact that permeates Brazilian society, especially the society of Amapa on a daily basis. The high rates of traffic accidents in the Capital of the State of Amapá are presented as a social phenomenon that instigates violence in traffic, taking the lives of countless people, causing socioeconomic problems to the political-administrative structure of the State and mainly the feeling of loss of families involved in traffic accidents. Faced with this reality, this work was constituted seeking to portray how this phenomenon occurs and its implications in the social bosom of Amapa, from a structured approach in three guiding topics of the development of the work, in which the first topic portrays an analysis at the national level of the constitution of traffic and its structure, in the second moment there will be a wide discussion regarding the reality of the structure of the traffic in Amapá, as well as the exposition of statistical data, finally an analysis based on the educational perspective as the most effective instrument to articulate measures aimed at reducing the rates of traffic accidents in the capital of Amapá.
Keywords: Amapá (Estado) - História; Estatística de trânsito; Acidentes de trânsito; Educação; CNPQ::CIENCIAS SOCIAIS APLICADAS